CT perfusion guided delayed recanalization with favorable outcome in pediatric stroke. (5th December 2011) - Xavier, Andrew; Kansara, Amit; Majjhoo, Aniel Q; Norris, Gregory
Abstract : There are no approved treatment options for acute ischemic stroke in the pediatric population. A case is presented of a 16-year-old boy with acute left-sided weakness who was transferred to our institution on the third day after onset of symptoms and after deterioration in his condition. He had right internal carotid artery occlusion beyond the origin of the ophthalmic artery. CT perfusion study showed a large area of penumbra in the right middle cerebral artery distribution. Recanalization was achieved with self-expanding stent placement and mechanical thrombectomy. Post procedure CT perfusion study showed resolution of the penumbra. At the 3 month follow-up, his modified Rankin Scale score was 1 and at 1 year it was 0. A subset of pediatric patients with acute ischemic stroke secondary to large intracranial arterial occlusion may be potential candidates for this treatment approach.